Production design and process of "Boys don't dance" - Mohammed Malik Abdul Karim (2017)
“Boys Don’t Dance” is a film about self-acceptance told through the main protagonist Ono who hopes to become a good ballet dancer one day. He practices alone when no one is around, as he gets mocked for doing so. On the other hand, he is in love with his best friend Ryan, but hesitates to confess his love for him as Ryan hides his homosexuality to not be looked down by his friends. Amidst this Ono gets transported to a fantastical world where he meets three circus freaks, who help him with self-realization.